My Favourite Prophet Muhammad Stories - Khan, Saniyasnain (Ajman,U.A.E Iqra book Distribution, 2024)
My Favourite Prophet Muhammad Stories relates fascinating stories about the Kabah and how the pilgrimage to it and trade with far-off lands such as Yemen, Syria, Iraq, Persia were organized along the silk route by the Prophet$1 (Bs great grandfather. Everything is covered from the re-digging of the Zamzam well to the year of elephants, to the birth of the Prophet Muhammad, and then on to his childhood in the desert and his early life in Makkah. This book encourages children to discover for themselves the message of the life of the Prophet and to find their own ways of applying the Prophet$1 (Bs timeless teachings to their lives.s
Keywords: Islamic books